A living lab co-creation environment exemplifying factor 10 improvements in a city district - Rosado, L.; Hagy, S.; Kalmykova, Y.; Morrison, Gregory; Ostermeyer, Y. (2015)
© Henry Stewart Publications. The greater proportion of global emission production and resource consumption takes place in cities. Innovations are needed to reduce the use of resources and emissions within the building sector, but the sector is slow to innovate and integrate new technology. In this paper, a district-scale approach is projected to be an effective way to invoke change within the built environment of a city system, exemplified through the European Union-funded Climate-KIC Smart Sustainable Districts (SSD) Flagship Project in Gothenburg, Sweden. The SSD aims increase to human wellbeing and economic vitality with 90% lower resource use resulting in a reduction in environmental impacts and associated greenhouse gas emissions. A co-creation environment is proposed to incorporate technology innovation for sustainable living into the district, and ultimately city, level which will be realised through the HSB* Living Lab Project, a living lab infrastructure under construction on the campus of Chalmers University of Technology. Interventions to reduce the use of resources at a district-scale systems level in combination with real-world testing and creation of innovative technology within living lab environments have the potential to effect a reduction in city system resource consumption and emissions. This pilot stage proposition will be tested through the implementation of both SSD and HSB Living Lab projects.